Caryophyllene-type sesquiterpenes from the endophytic fungus Pestalotiopsis lespedezae through an OSMAC approach - Yu, Xiaoqin; Müller, Werner E. G.; Frank, Marian; Gao, Ying; Guo, Zhiyong; Zou, Kun; Proksch, Peter; Liu, Zhen (Frontiers in Microbiology, 2024)
Two new caryophyllene-type sesquiterpenes pestalotiopsins U and V (1 and 2) and three known compounds pestalotiopsin B (7), pestaloporinate B (8), and pestalotiopsin C (9) were isolated by the cultivation of the endophytic fungus Pestalotiopsis lespedezae on solid rice medium, while four additional new caryophyllene pestalotiopsins W–Z (3–6) were obtained when 3.5% NaI was added to the fungal culture medium. The structures of the new compounds were determined by HRESIMS and 1D/2D nuclear magnetic resonance data. Compounds 1–9 were tested for cytotoxicity against the mouse lymphoma cell line L5178Y, but only 6 displayed significant activity with an IC50 value of 2.4 μM.